Pengaruh media tanam dan metode aplikasi zat pengatur tumbuh terhadap keberhasilan setek akar sukun (Artocarpus Altilis Fobs.) - Paskalius Aprianto Merahabia; Baso Daeng; Veronika Lenora Tuhumena; Herman Wafom Tubur (Agrotek, 2020)
This study aims to observe the growth of breadfruit root cuttings due to a combination of planting media and the application of growth regulators. The research was carried out experimentally using a randomized block design with 9 treatments, namely soil, soil + PGR soaking, soil + PGR powder dipping, husk + soil, husk + soil + PGR soaking, husk + soil + PGR powder dipping, sand + soil, sand + soil + PGR soaking, sand + soil + PGR powder dipping. The data obtained were analyzed statistically and test futhered by Tukey's honestly significant difference. The results found that there were significant different in the characters of shoot time, shoot length 1-6 WAP, number of shoots, and number of roots. The treatment of soil media and PGR dipping performed the fastest shoot time. On the other hand, a mixture of soil with husk and ZPT given by soaking showed the best shoot length. The most roots number was produced by the the cuttings planting in sand and treated by dipping PGR.